PERBANDINGAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE DAN PICTURE AND PICTURE PADA MATERI SISTEM PERNAPASAN DI KELAS VIII SMP NEGERI 2 DOLOK PANRIBUAN - Sitompul, Wasteria; Huda, M. Komarul (Jurnal Metabio, 2021)
This study compares student learning outcomes using the Example-Non-Example and Picture and-Picture learning models on the Respiratory System in eighth-grade students at SMP Negeri  2 Dolok Panribuan. This study aims to determine whether there are differences in student learning outcomes when learning about the respiratory system using the Example-Non-Example and Picture-and-Picture models, and to determine the magnitude of the differences in student learning outcomes when learning about the respiratory system using the Example-Non-Example and Picture-and-Picture models. The population in this study was all eighth-grade students in the second semester of SMP Negeri 2 Dolok Panribuan in the 2019/2020 academic year, consisting of six classes with a total of 179 students. Sampling was conducted using cluster random sampling. The sample taken in this study was divided into two classes: class VIII-2 (experimental class I) using the Example-Non-Example learning model and class VIII-5 (experimental class II) using the Picture-and-Picture learning model. Data analysis was performed by calculating the average score and standard deviation, and hypotheses were tested using the t-statistic or t-test at a significance level of α = 0.05. Based on the research results obtained, the total pre-test and post-test scores for experimental class I were 1350 and 2670 while the average scores were 42.18 and 83.43. In experimental class II the total pre-test and post-test scores for experimental class II were 1470 and 2485 while the average scores were 45.93 and 77.65. When comparing the average post-test value of experimental class I (83.43) with experimental class II (77.65), a difference in student learning outcomes was obtained of 5.78 where the learning outcomes of experimental class I with the Example Non Example model were higher than the learning outcomes of experimental class II with the Picture and Picture learning model. The results of hypothesis testing using the "t test" at a significance level of α = 0.05 and (dk) = 58 obtained t count (2.50> t-table (1.99) then Ho was rejected, Ha was accepted meaning there was a difference in student learning outcomes using the Example Non Example and Picture and picture learning models on the respiratory system material in class VIII of SMP Negeri 2 Dolok Panribuan in the 2019/2020 academic year.